Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/003804070808100103
|View full text |Cite
|
Sign up to set email alerts
|

School Strategies and the “College-Linking” Process: Reconsidering the Effects of High Schools on College Enrollment

Abstract: This study reconsidered school effects on college enrollment by focusing on strategies that schools use to facilitate college transitions. It also examined whether school strategies influence different outcomes for students from different racial/ethnic and socioeconomic backgrounds. Using data from the High School Effectiveness Study, the analysis identified three distinctive "college-linking" strategies: traditional, clearinghouse, and brokering. The results revealed that the strategies that schools use to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(37 citation statements)
references
References 29 publications
(48 reference statements)
0
28
0
4
Order By: Relevance
“…American research has indicated the way in which schools can adopt different strategies of linkage with universities, in some cases acting as 'brokers' in the transition process (Hill 2008). The system of higher education application in Ireland is more centralised, allowing less room for the school to intervene directly in the process.…”
Section: Discussionmentioning
confidence: 99%
“…American research has indicated the way in which schools can adopt different strategies of linkage with universities, in some cases acting as 'brokers' in the transition process (Hill 2008). The system of higher education application in Ireland is more centralised, allowing less room for the school to intervene directly in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows the importance of different social networks in increasing the likelihood of college attendance, with particular attention to parent, peer, and other college-linking networks (Engberg & Allen, 2011;Engberg & Wolniak, 2010;Hill, 2008;Pérez & McDonough, 2008;Perna & Titus, 2005). Disparities, however, exist in relation to students' access to different social networks, and studies show that economically advantaged students have greater access to private counselors (McDonough, 1994), take college entrance examinations more frequently (Fitzgerald & Delaney, 2002), and attend high schools with more established college feeder relationships (Wolniak & Engberg, 2007).…”
Section: Models Of College Choicementioning
confidence: 99%
“…Al referirnos a estrategias institucionales de los establecimientos secundarios, utilizamos indicadores que la literatura internacional señala como relevantes en este ámbito (Hossler et al, 1999;McDonough, 1997, Engberg y Wolniak, 2010, Reay, David y Ball, 2001, que forman parte de los recursos y normas que el colegio pone a disposición de los alumnos para favorecer su ingreso a la universidad (Hill, 2008;Draelants, 2011). Para ello utilizamos indicadores provenientes del cuestionario aplicado a los alumnos, relativos a recursos curriculares (preparación académica específica para enfrentar los estudios universitarios) y normas organizacionales (orientación en torno a los estudios universitarios, confianza para tomar decisiones, motivación y apoyo entregado por los profesores para seguir estudios universitarios).…”
Section: Principales Resultadosunclassified
“…En estas investigaciones se refleja el aporte de los análi-sis cuantitativos pero también de metodologías cualitativas, más recientes en este tipo de estudios (Hossler, Kinzie, Palmer, Hayek, Jacob y Cummings, 2004). Una segunda corriente la constituyen aquellos estudios que investigan específicamente la relación entre el contexto escolar y el acceso a la universidad (Perna, 2006;Hill, 2008;Engberg y Wolniak, 2010).…”
Section: Las Estrategias Institucionales De Los Establecimientos Secuunclassified
See 1 more Smart Citation